Pelaksanaan Supervisi Sekolah Antara Fakta Dan Idealita Di SDN 04 IX Korong, Kota Solok - gusnita, fitria gusnita; Jamilus, Jamilus (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to identify the gap between the implementation of school supervision at SDN 04 IX Korong Solok City and the expected ideals based on educational supervision theory and national regulations. The approach used was descriptive qualitative with research subjects including principals, teachers and supervisors. Data were collected through in-depth interviews, field observations and documentation studies, then analyzed using data reduction, data presentation and conclusion drawing techniques. The results showed that the supervision carried out was still administrative in nature, less systematically planned, minimal follow-up, and had less significant impact on improving the quality of learning. The limited competence of supervision implementers and the lack of teacher participation are the main inhibiting factors. Therefore, this study recommends increased training for principals and supervisors, the application of a more collaborative supervision approach, and the provision of adequate supporting resources so that supervision can run effectively and sustainably. The findings are expected to serve as a reference in improving the education supervision system at the elementry school level.